Lagged response of summer precipitation to solar activity in the mid-lower reaches of the Yangtze River - Li, Hui; Wang, Yuting; Wang, Chi (Frontiers in Earth Science, 2023)
In the context of more frequent extreme precipitation worldwide, the sun's influence on global or regional rainfall patterns has attracted much attention. Due to its vital importance to Chinese industrial and agricultural production, the precipitation property in the mid-lower reaches of the Yangtze River (MLRYR) remains a hot issue. Although previous works have implied the plausible influence of solar activity on precipitation in the MLRYR, the time-lagged effect is still an open question. In this paper, we adopt the China-Z index (CZI) to represent the original precipitation data, which is proposed to monitor moisture conditions over China and is more sensitive to solar activity. We explore the lagged correlations between summer precipitation in the MLRYR and solar activity. The CZI in June-July is negatively correlated with the sunspot number in July of the preceding year, giving a time lag of 11 months. Based on the composite analysis, we suggest that solar activity possibly modulates the precipitation by influencing the local moisture and its vertical movement through the sea-land thermal contrast and the associated East Asian summer monsoon on a much larger scale.